PROTECTIVE ROLE OF CRUDE EXTRACT OF AMORPHOPHALLUS CAMPANULATUS AGAINST ETHANOL-INDUCED OXIDATIVE RENAL DAMAGE - Basu, Subhashree; Das, Moumita; Sen, Anurupa; Datta, Gouriprosad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: The current study investigates the nephroprotective effect of Amorphophallus campanulatus against chronic alcohol-induced oxidative stress and tissue damage. Methods: The rats were simultaneously supplemented with ethanolic extract of A. campanulatus along with ethanol (40% w/v)2 g/kg body weight/day for 30 days to evaluate the nephroprotective effect against alcohol toxicity. Renal antioxidant enzymes, serum urea, creatinine, and pro-inflammatory cytokines were assayed biochemically. Histomorphological and histochemical alterations were detected by Hematoxylin and Eosin, periodic acid Schiff, and Feulgen and Picrosirius stain, respectively. The degree of apoptotic cell death was examined by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay technique. Results: Serum urea, creatinine, pro-inflammatory cytokines, tissue TBARS, and activity of glutathione metabolizing enzymes were significantly (p<0.01) elevated, whereas cytosolic and mitochondrial superoxide dismutase, catalase, and levels of reduced glutathione were significantly (p<0.001) decreased in the EtOH group compared to control. However, ethanolic extract of A. campanulatus (ACE) supplementation to the EtOH rats reversed these effects to normal levels. Furthermore, degenerative changes in renal cells with alcohol treatment were minimized to nearness in architecture by ACE supplementation. Glycogen and deoxyribonucleic acid depletion, excess fibrosis due to collagen deposition, and increased apoptotic cell number were also restricted by ACE supplementation, with the higher dose being more promising. Conclusion: Thus ethanol-induced nephrotoxicity was attenuated by ACE treatment by the antioxidative and antiapoptotic property of the extract. Such effects of the extract may be due to the probable presence of different bioactive components in the tuber. Hence, it can be used as a regular nutrient or therapeutic agent to protect the renal cells.